Análise de resultados intermediários das políticas de bônus em escolas públicas estaduais brasileiras - Bresolin, Antonio Bara (2014)
Between 2008 and 2011 bonuses program for people who work at state schools was implemented by a number of different Brazilian states. The aim was to stimulate the improvement of students’ performance. The objective of the present study is to evaluate the impact of those programs in 3 dimensions: 1 - teachers’ pedagogic practices, 2- absenteeism and teachers’ rotation, 3- interlocution with family members in order to ensure students’ presence at school. Data were collected from the Prova Brasil (Brazil Test) questionnaire, which was answered by principals, teachers and students from the treatment group schools and from the control group. The following items were taken into consideration: the variation in the years of implementation of the programs (dose), their difference in kind (type) and the different grades students were in (grade). The methodological approach for the proposed analysis was matching based on propensity score, followed by the calculation of differences in difference between the states that implemented this policy and those which did not. The results vary according to the grade and dose, with a positive impact in some of the categories of analysis: in dimension 1, there was an impact related to how often teachers correct homework; in dimension 2, results point to a reduction in director’s concern over teacher’s rotation and an increase in the perception that teacher’s absenteeism is a feature of the reality of state schools in Brazil; as for dimension 3, data reveal no significant impact. There is no conclusive evidence that financial reward is an efficient and successful way of promoting change in directors’ and teachers’ behavior, a change that would achieve intermediate results in the improvement of students’ learning skills.